Büyük Selçuklular Devrinde Kadıların Maaşları, Gelir Kaynakları ve Maddî Durumları Üzerine Bir Araştırma - Sinan TARİFCİ (Gazi Akademik Bakış)
In the Great Seljuqs period, the qadis, who were the main officials of the justice organization, had a wide scope of duties and activities within their judicial, political, administrative, military, religious, social, etc. powers and responsibilities. Thus, in this period, as a result of a large task union, office of the qadi went beyond merely being an office of judiciary and fulfillment of legal affairs. The qadis received a salary for the judicial duty they fulfilled, as well as earning income from the duties and activities they performed outside of their main duties. In addition to the income earned from the salary for the judicial duty and additional duties, the qadis could also gain various allowances and grants that would lead them to wealth rather than a certain quality of life. However, legal discussions about whether the qadis could receive a salary and accept donations as gifts had continued since the early periods of Islam, including the considerations of the scholars and ideologues of the Great Seljuk period. On the other hand, despite the administrative, religious and moral pressure, there were also those who made illegal profit, especially bribery, among the qadis. Among the Seljuk qadis, there were also the qadis who lived a luxurious life in wealth, as well as living in poverty and barely maintaining their lives. In this study, salaries, income sources and financial situations of the qadis in the Great Seljuqs period are going to be examined. By doing this, the subject is going to be discussed within its theoretical perspective and practical processes.